The German legal system - Freckmann, Anke (Sweet and Maxwell, 1999)
The book describes the history and development of German law as well as explaining existing court systems and the structure of the judiciary. To assist understanding, comparisons with the English legal system are drawn throughout and a glossary of terms is included at the end of the book